Comparative Simulation Study on Synchronous Generators Sudden Short Circuits. (14th July 2009) - Lupşa-Tătaru, Lucian
Abstract : Although of a great extent in time, the research works directed at studying transients in synchronous generators have not yet provided fully sufficient comparative studies in respect to sudden short circuits of the machine. The present paper puts forward novel and comprehensive process models for dynamic simulation of short circuit faults of initially unloaded synchronous generators, using the generalized d - q -0 mathematical model as starting point in derivation. Distinct from the time-domain analysis, the technique proposed here allows an effective comparative overview by employing a specialized procedure to perform repeated time-domain simulations accompanied by peak values recording for the various circumstances. The time consuming matrix numerical inversion at each step of integration, usually performed when selecting currents as state variables, is eliminated by advancing the process models in a convenient split matrix form that allows the symbolic processing. Also, the computational efficiency is being increased by introducing a set of auxiliary variables common to different state equations. The models derivation is carried out without altering the structural equations of the generalized d - q -0 mathematical model of synchronous generators whilst the simulation results are both compared and discussed in detail.